Utilization of Herbal Medicine for Hemorrhoids - Nur Laili Kurniawati Rofiqoh; Norainny Yunitasari (Media Farmasi Indonesia, 2024)
Hemorrhoids is a disease characterized by swollen blood vessels in the rectum or anus. This disease is caused by low consumption of fiber, spicy foods and alcoholic drinks. Symptoms that can be experienced by hemorrhoid sufferers are the appearance of lumps and bleeding when defecating. One treatment for this disease is through the use of herbal medicine, namely purple leaves. The aim of this research is to prove whether people now also use purple leaves as a treatment for hemorrhoids. This type of research is non-experimental using survey methods. The instrument used was a questionnaire. The research results show that the majority of hemorrhoid sufferers (80%) use purple leaves to reduce hemorrhoid symptoms. The price of purple leaf medicine is very competitive with conventional hemorrhoid medicine, so that 52% of hemorrhoid sufferers consume purple leaf regularly (although not when experiencing hemorrhoid symptoms).